Inovasi Kurikulum dan Peningkatan Profesionalitas Guru - Ahmad Darlis; Hadad Alwi; Bulan Hasibuan; Muhammad Arif Syuhada; Viona Miftahuljannah (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
Globalization breeds a flood of unusually fast progress moreover, change is a necessity. To face the challenges and open doors in the era of globalization, especially globalization Training is expected to cause an uproar around the world of cities by 2030 and invite Indonesia Emas 2045, Indonesian public authorities are given various improvement strategies compiled by the nature of training, to have the option to compete seriously and be able to. There are two very imaginative issues in the instruction field, to be more specific: the approach to the development of educational programs is described by the introduction of the Education program 2013 and the structuring of the simultaneous expansion of abilities of impressive instructor skills. These two approaches should work together to trap people who are clever and have character. An intelligent individual is an individual who is deeply intelligent, mentally, socially and sincerely, while an individual with character is a person who can realize character values starting from religious lessons and pancasila as a